Repeatability and agreement of multispectral refraction topography in school children before and after cycloplegia - Xiaoli Xu; Wansheng Zang; Anken Wang; Chenhao Yang (BioMedical Engineering OnLine)
Abstract Background The purpose of this study was to evaluate the repeatability and agreement of multispectral refraction topography (MRT) in measuring retinal refraction before and after cycloplegia in children. The results of this study will provide valuable insights into the accuracy and reliability of MRT as a tool for assessing retinal refraction in pediatric patients. Methods Children aged 7 to 18 years old were recruited for this prospective research. The central and peripheral retinal refraction was measured three times using multispectral refraction topography (MRT) before and after cycloplegia. The retinal deviation value (RDV) was used to describe the average peripheral refractive error of the retina. In addition, objective refraction (OR) and subjective refraction (SR) measurements were also performed. Results A total of 60 children with a mean age of 10.50 ± 1.81 years were enrolled. Before cycloplegia, all the central and peripheral retinal refraction parameters showed good repeatability with the lowest intraclass correlation coefficient (ICC) being 0.78 in the retinal deviation value from 45° eccentricity to 53° of the retina (RDV 45–53). After cycloplegia, the repeatability of MRT was significantly enhanced (lowest ICC = 0.91 in RDV-I). The 95% limits of agreement (LoA) of the central refraction and OR ranged from − 2.1 to 1.8 D before cycloplegia, and from − 1.69 to 0.27 D after cycloplegia. The 95% LoA of the central refraction and SR ranged from − 1.57 to 0.36 D after cycloplegia. All the 95% LoA demonstrated high agreement. Conclusions The MRT shows high agreement with autorefractometry and experienced optometrist in measuring central refraction. Additionally, the MRT provides good repeatable measurements of retinal peripheral refraction before and after cycloplegia in schoolchildren.